Using and Abusing the Holocaust - Langer, Lawrence L. (Book collections on Project MUSE., 2006)
"All of the essays in Using and Abusing the Holocaust consider Holocaust-related issues, but many of them are also concerned with a problem that affects consciousness in the modern era: how to go on living fruitfully amidst almost daily announcements of unnatural or violent death. Several examine reasons for the exaggerated importance still given to Anne Frank's Diary as a Holocaust narrative, for the uncritical acclaim awarded Binjamin Wilkomirski's fake memoir, Fragments, and for the different approaches to "justice" adopted following the Holocaust and the collapse of the apartheid regime in South Africa."--Jacket